Thermal Analysis Of Non-Newtonian Fluid Flow Over Superhydrophobic Surface - Gan, Zheng Ho (Universiti Sains Malaysia, 2019)
The advancement of technology has led to the demand for hydrophobic surface coating and miniature components. However, recent studies only reveal the effects of superhydrophobic surface on Non-Newtonian fluid for circular channel. Hence, there is a need for further the understanding of another type of channel (i.e, plane channel). This study presents a numerical investigation on the hydrodynamic entrance length and thermal entrance length of power-law fluid for planar channel flow consists of alternating superhydrophobic grooves and ribs arranged parallel to the flow direction. The simulations were performed in low Reynolds number range 0.001<Re<100, for power-law index in the range of 0.5<n<1.5 with dimensionless gas area fraction in the range of 0.125<